Shakespoke: Selves, Others, and Folk Poetry - Greenhill, Pauline (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1993)
This essay introduces the six papers in this special issue by comparing the writers’ construction of analytical and rhetorical distance from their subjets — folk poetry and folk poets — in terms of concepts of self and other. It focuses upon folklorists as the (re)producers of cultural texts, not only as their disengaged audience.